Different training patterns and bone mineral density of the femoral shaft in elite, female athletes. Issue 7 (July 1991) - Wolman, R L; Faulmann, L; Clark, P; Hesp, R; Harries, M G
Abstract : The effects of sporting activity and of menstrual status on the bone mineral content of the femoral mid-shaft were investigated. The cohort consisted of 67 elite, female athletes comprising 21 runners, 36 rowers, and 10 dancers. Twenty five of these athletes were amenorrhoeic, 27 eumenorrhoeic, and 15 were taking the oral contraceptive. The bone mineral content was also measured in 13 eumenorrhoeic, sedentary women. The mean (95% confidence interval) bone mineral content in the runners was 1.51 (1.47 to 1.55) g/cm2, which was significantly higher than in the rowers, dancers, and sedentary controls whose values were 1.43 (1.40 to 1.47), 1.39 (1.33 to 1.45), and 1.40 (1.34 to 1.45) g/cm2 respectively. There was no significant difference in the bone mineral content between the amenorrhoeic, eumenorrhoeic, and oral contraceptive taking athletes. These results may have implications for devising exercise strategies to reduce the possibility of fractures in later life.